The Effect of Compensation, Leadership Style, Work Environment, And Work Motivation On Employees Job Satisfaction in Civil Registration Offices - Hikmah Abelia Utami; Suyoto Suyoto; Fatmah Bagis; Dian Widyaningtyas (Jurnal Ekuilnomi, 2026)
This study aims to analyze the influence of compensation, leadership style, work environment, and work motivation on employee job satisfaction at the Department of Population and Civil Registration of Banyumas Regency. This research employs a quantitative method with primary data collection through a 5-point Likert scale questionnaire. The sampling technique uses saturated sampling with a population of 91 employees, resulting in a sample of 90 employees, excluding the Head of Department due to their different structural role. Data analysis uses Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software version 3.0. The results indicate that compensation does not significantly influence employee job satisfaction, while leadership style, work environment, and work motivation have a positive and significant influence on employee job satisfaction. These findings contribute to the Human Resource Management literature by emphasizing the importance of leadership quality, work environment, and internal motivation as key factors shaping employee job satisfaction.